A study on the Fatigue behavior of Heat Treated Aluminium Hybrid Metal Matrix Composites(Al6061-SiC-Gr) - et. al., Ali Afzal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Aluminum alloys are widely used as a choice for aerospace, automotive and structural applications due to their high strength to weight ratio and high wear resistance. This research work is aimed at investigating the impact of heat treatment and age hardenability on the fatigue behavior of Aluminum Hybrid Metal Matrix Composites(AHMMC). The composite was produced with Aluminum alloy 6061 as base material with varying reinforcement of x weight percentages (1wt% and 3wt%) of graphite and fixed value of 5wt% of Silicon Carbide. Fabrication of AHMMC was carried out using a vortex stir casting technique with a stirring speed of 400 rpm for 1 minute and a temperature of 700℃ to 800℃. Microstructure, X-ray diffraction, microhardness and fatigue strength studies were conducted for different percentages of reinforcement on the fabricated stir cast AHMMC specimen before and after the heat treatments. Fractography was also performed to study the fractured surfaces of the AHMMC. Microstructure and XRD study revealed that both SiC and Gr are uniformly distributed in the matrix alloy. The microhardness of Al-SiC was higher than that of hybrid composites and base alloys. Heat treatment increased the microhardness of base alloy and its hybrid composites while ice quenching treatment resulting in maximum value. The fatigue strength of heat-treated AHMMC was higher than that of Al-SiC composites and base alloys without heat treatment. Fractography results suggest that fatigue failures are reduced with the addition of SiC and Gr.